2020
DOI: 10.1101/2020.11.15.383463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2-specific T cell memory is long-lasting in the majority of convalsecent COVID-19 individuals

Abstract: An unaddressed key question in the current coronavirus disease 2019 (COVID-19) pandemic is the duration of immunity for which specific T cell responses against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are an indispensable element. Being situated in Wuhan where the pandemic initiated enables us to conduct the longest analyses of memory T cell responses against SARS-CoV-2 in COVID-19 convalescent individuals (CIs). Magnitude and breadth of SARS-CoV-2 memory CD4 and CD8 T cell responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
2
7
1
1
Order By: Relevance
“…This assumption is supported by an observation from Wuhan, China, where the majority of COVID-19 patients also showed a decrease in T-cells directed against SARS-CoV-2 in a biphasic manner. Comparable to our study, the Chinese study found a loss of specific CD8 T-cells in 26% of convalescents and a loss of specific CD4 helper cells in only 16% after 9 months [32].…”
Section: Discussioncontrasting
confidence: 64%
“…This assumption is supported by an observation from Wuhan, China, where the majority of COVID-19 patients also showed a decrease in T-cells directed against SARS-CoV-2 in a biphasic manner. Comparable to our study, the Chinese study found a loss of specific CD8 T-cells in 26% of convalescents and a loss of specific CD4 helper cells in only 16% after 9 months [32].…”
Section: Discussioncontrasting
confidence: 64%
“…In addition to a humoral mediated immune response, T cell-mediated immune response plays a role in SARS-CoV-2 infection and the specific cellular immunity may be more stable and longer lasting than humoral immunity [ 38 , 39 ]. This is particularly of interest regarding the immunity of recovered patients with low or no detectable neutralizing antibodies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have confirmed the presence of SARS-CoV-2 specific CD4 T cells in recovered patients in the ADAPT Study at St Vincent's Hospital, Sydney, using the OX40 assay, but like other studies, have found that about half of healthy non-COVD-19 controls had responses to pools of peptides from the full SARS-CoV-2 spike protein sequence, presumably cross-reacting with endemic coronaviruses 54 . SARS-CoV-2 specific memory CD4 and CD8 T cells were still present in recovered patients at 9 months after symptom onset in one study 55 , and at 6-8 months in another study, with an apparent halflife of only 3-5 months 56 .…”
Section: T-cell Responses In Sars-cov-2 Infectionmentioning
confidence: 90%